2015
DOI: 10.3163/1536-5050.103.2.006
|View full text |Cite
|
Sign up to set email alerts
|

Health sciences librarians, patient contact, and secondary traumatic stress

Abstract: Library and employee assistance program managers should be aware of the emotional toll of patient and/or family contact for HSLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Individual studies focusing on the impacts of vicarious trauma among other related professional and/or volunteer groups, listed in order of publication year, include: Kiyimba and O’Reilly (2016) for qualitative transcriptionists; Coleman, Delahanty, Schwartz, Murani, and Brondolo (2016) for medical examiner office employees; Becker and McCrillis (2015) for health sciences librarians; Lusk and Terrazas (2015) for para-professionals working with refugees; Mehus and Becher (2016) for spoken-language interpreters; Ewer, Teesson, Sannibale, Roche, and Mills (2015) for alcohol and other drug workers in Australia; Dasan, Gohil, Cornelius, and Taylor (2015) among emergency medical consultants; Fisackerly, Sira, Desai, and McCammon (2016) among certified child life specialists; Mishori, Mujawar, and Ravi (2014) for asylum evaluators; Johnson, Bertschinger, Snell, and Wilson (2014) for military psychologists; Furlonger, and Taylor (2013) for telephone and online counselors, Želeskov-Ðorić, Hedrih, and Ðorić (2012) for psychotherapists; Levin et al (2011) for attorneys and their administrative support staff; Negash and Sahin (2011) for marriage and family therapists; Robertson, Davies, and Nettleingham (2009) for jurors; and Figley and Roop (2006) for animal caregivers.…”
Section: Steps 1 and 2 Of A Public Health Approach: Defining The Prob...mentioning
confidence: 99%
“…Individual studies focusing on the impacts of vicarious trauma among other related professional and/or volunteer groups, listed in order of publication year, include: Kiyimba and O’Reilly (2016) for qualitative transcriptionists; Coleman, Delahanty, Schwartz, Murani, and Brondolo (2016) for medical examiner office employees; Becker and McCrillis (2015) for health sciences librarians; Lusk and Terrazas (2015) for para-professionals working with refugees; Mehus and Becher (2016) for spoken-language interpreters; Ewer, Teesson, Sannibale, Roche, and Mills (2015) for alcohol and other drug workers in Australia; Dasan, Gohil, Cornelius, and Taylor (2015) among emergency medical consultants; Fisackerly, Sira, Desai, and McCammon (2016) among certified child life specialists; Mishori, Mujawar, and Ravi (2014) for asylum evaluators; Johnson, Bertschinger, Snell, and Wilson (2014) for military psychologists; Furlonger, and Taylor (2013) for telephone and online counselors, Želeskov-Ðorić, Hedrih, and Ðorić (2012) for psychotherapists; Levin et al (2011) for attorneys and their administrative support staff; Negash and Sahin (2011) for marriage and family therapists; Robertson, Davies, and Nettleingham (2009) for jurors; and Figley and Roop (2006) for animal caregivers.…”
Section: Steps 1 and 2 Of A Public Health Approach: Defining The Prob...mentioning
confidence: 99%
“…9 Comparison of scores of professionals with similar levels of patient contact, such as social workers, yielded analogous results. Despite the lack of additional qualitative investigation, Becker and McCrillis’ study demonstrates that clinical librarians experience significant emotional stress due to involvement in direct patient care.…”
Section: Introductionmentioning
confidence: 83%
“…Trauma curriculum students and teachers have been affected adversely, reporting a variety of negative physical and psychological reactions (Fucci, 2008;Lucas, 2008). Becker and McCrillis (2015) reported moderate levels of STS in a sample of health sciences librarians in direct contact with individuals and their families who had experienced trauma. Ludick (2006) found that as much as 43% of a sample of short-term insurance claims workers, a purely administrative group of employees, expressed disturbing levels of STS.…”
Section: Early Investigations and Conceptualizationsmentioning
confidence: 99%